EFEKTIVITAS RELAKSASI AUTOGENIK TERHADAP DYSMENORRHEA - Nurteti Putri Dewi; Sri Utami; Sofiana Sofiana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Dysmenorrhea is an excessive pain during menstruation caused by uncoordinated uterinecontrauctions. There were some pain managements for dysmenorrhea, one of them was autogenicrelaxation. This study aims to determine the effectiveness autogenic relaxation against the intensityof dysmenorrhea. The research design used in this study was “pre- experiment” with “one grouppretest-postest” only. The sample in this research were the VII grade students of Junior HighSchool 3 Pekanbaru, the total sample were 17 experiment respondendents who taken by usingaccidental sampling techniques. The measuring instrument used was observation sheets. Theanalysis were univariate and bivariate analysis by using Wilcoxon tests. The result showedsignificant reduction of intensity dysmenorrhea on experimental group after the group has given therelaktation autogenic with p value (0,000) < ά (0,05). It means autogenic relaxation was effective toreduce the intensity of dysmenorrhea. The result of this study is expected to be an alternative tohandling the dysmenorrhea for young women.Keyword: Autogenic relaxation, dysmenorrhea, menstruation